Comparison of Angiographic Findings in Diabetic and Non-Diabetic Female patients presenting with Acute Coronary Syndrome at a Tertiary Cardiac Care Center in Karachi, Pakistan - Muhammad Faizan Siddiqui, Hassan Khan, Muhammad Rahman Khalid, Asad Aslam Korejo, Farwa Faizan, Akram Yousif, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: -To evaluate the angiographic differences in female patients and to compare the frequency of different angiographic findings in diabetic and non-diabetic female cases with acute coronary syndrome. Place and Duration of Study: Department of Adult Cardiology, Tabba Heart Institute Karachi, Pakistan from 1st February 2018 to 31st August 2018 Study design: Cross-sectional study Methodology: Two hundred patients presenting with acute coronary syndrome undergoing angiography with diabetes mellitus and non-diabetes mellitus were enrolled. Demographic profile of the cases was recorded Angiography was performed by experienced cardiologist for all patients. Study outcome, number of vessels involved, type of vessels, was recorded for all patients. All the collected information was recorded using pre-designed structural questionnaire. Results: 67% were diabetic and 23% were non-diabetic. In diabetic group single vessel disease was observed in 29 (23%), 2 vessel disease in 37 (29.4%) and 3 vessel disease in 49 (38.9%) while in non-diabetic group single vessel disease, 2 vessel disease and 3 vessel disease was observed in 24 (32.4%), 19 (25.37%) and 19 (25.7%) respectively (P=0.092). Three vessel disease involving LAD+ Circumflex+ RCA is 49 [38.88%] and 19 [25.67%] in diabetic and non-diabetic group respectively. Three-vessel disease was more prevalent in diabetics but it was not statistically significant (p=0.092). Conclusion: Three vessel diseases is most frequently present as angiographic finding in female patients presenting with acute coronary syndrome. Keywords: Acute coronary syndrome (ACS), Diabetes mellitus (DM), Unstable angina, ST-elevated myocardial infarction